The Influence of Job Demand and Job Resources on Job Satisfaction Mediated by Work-Life Balance Among Employees at PT. Daya Tani Sembada (Rice Milling) - Doni Ismail Awang Santoso; Moch. Tutuk Safirin (Advance Sustainable Science Engineering and Technology, 2025)
One form of employee behavior is the desire to leave (turnover), where employees decide to leave their jobs. The employee turnover rate over the past three years at PT. Daya Tani Sembada has been above the normal limit each year, indicating that the company's turnover is high. This may suggest potential issues in human resource management or a mismatch between employees and the organization. Due to the high turnover rate, the company needs to conduct recruitment to replace these employees in order to maintain performance levels. Therefore, the researcher aims to understand the influence using the Partial Least Squares (PLS) method. Based on this research, it can be determined that job demands influence job satisfaction mediated by the work-life balance variable, and there is no influence of job resources on job satisfaction mediated by the work-life balance variable.